Internal NeurolysisVersus Ligament Division in Carpal Tunnel Syndrome Surgery - Ahmed, Abdulrahman Saeed; Hussein, Yasin Thamer (Diyala Journal of Medicine, 2018)
Background: Carpal tunnel syndrome is a compression neuropathy of median nerve at the wrist underneath the flexor retinaculum ligament. It is extremely more common in females than males and usually responds to conservative line of treatment and surgery is recommended after failure of the conservative treatment . Objective: To evaluate the effect of internal neurolysis on the clinical outcome of carpal tunnel surgery. Patients and Methods: Forty-eight patients with clinically proved carpal tunnel syndrome were divided into two equal groups; group A were submitted to division of flexor retinaculum ligament only while group B underwent internal neurolysis in addition to division of flexor retinaculum. The two groups have been compared postoperatively on clinical basis for an average period of (4) months. The study had been done prospectively in the period from January 2014 to August 2016 in Ba´quba Teaching Hospital. Results: All the cases had beensatisfied with the outcome of surgery in both groups,with recurrence in one case only in group A which responded well to conservative treatment. Conclusion: There was no significant difference in the outcome of both groups in which the addition of internal neurolysis is not necessary and it had no striking effect on the outcome of carpal tunnel surgical decompression.